2013
DOI: 10.1155/2013/152786
|View full text |Cite
|
Sign up to set email alerts
|

LOX-1, OxLDL, and Atherosclerosis

Abstract: Oxidized low-density lipoprotein (OxLDL) contributes to the atherosclerotic plaque formation and progression by several mechanisms, including the induction of endothelial cell activation and dysfunction, macrophage foam cell formation, and smooth muscle cell migration and proliferation. Vascular wall cells express on their surface several scavenger receptors that mediate the cellular effects of OxLDL. The lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) is the main OxLDL receptor of endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
511
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 626 publications
(523 citation statements)
references
References 96 publications
8
511
0
4
Order By: Relevance
“…However, although we found no significant correlation between plaque OLR1 mRNA levels and sLOX‐1 in plasma, lack of statistical correlations do not rule out any causal relationship. Indeed, the regulation of membrane‐bound LOX‐1 and its release into the circulation is modified by numerous stimuli, such as cytokines, modified lipoproteins, statins, and metalloproteinases 1, 3, 28, 29, 30. Therefore, it is not unlikely that there is a nonlinear relationship between plaque mRNA levels of OLR1 and the amounts of sLOX‐1 that are shed from the atherosclerotic lesions into the circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although we found no significant correlation between plaque OLR1 mRNA levels and sLOX‐1 in plasma, lack of statistical correlations do not rule out any causal relationship. Indeed, the regulation of membrane‐bound LOX‐1 and its release into the circulation is modified by numerous stimuli, such as cytokines, modified lipoproteins, statins, and metalloproteinases 1, 3, 28, 29, 30. Therefore, it is not unlikely that there is a nonlinear relationship between plaque mRNA levels of OLR1 and the amounts of sLOX‐1 that are shed from the atherosclerotic lesions into the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…LOX‐1 is regarded as the main oxidized low‐density lipoprotein scavenger receptor of endothelial cells, and is also expressed on the cell surface of other cells involved in the pathogenesis of atherosclerosis, such as monocytes/macrophages and smooth muscle cells (SMC) 1. Although the basal expression of LOX‐1 is low, it is induced by oxidative and inflammatory stimuli 1. Membrane‐bound LOX‐1 can be proteolytically cleaved into a soluble form.…”
mentioning
confidence: 99%
“…LOX-1 expression is induced by ligand binding via intracellular signaling in multiple pathological states, such as atherosclerosis, obesity, inflammation and in cellular transformation and carcinogenesis [14,26]. Its activation triggers the oxidative stress response causing plaque vulnerability and potential rupture, which leads to acute atherothrombotic vascular occlusion and tissue infarction [37,59]. The higher local concentration of ox-LDL, together with the higher expression of LOX-1 receptor, in atherosclerotic lesions, provides a molecular basis linking ox-LDL to endothelial cells and the resultant cellular activation, dysfunction, and injury.…”
Section: S Raniolo Et Al / Cholesterol Level Regulates Lectin-likementioning
confidence: 99%
“…Under physiological conditions, basal cellular LOX-1 expression is low in most tissues, while it is up-regulated in several pathophysiological processes such as inflammation, atherosclerosis, obesity and diabetes [59,68]. In this context, LOX-1 and ox-LDL contribute to plaque rupture in atherosclerosis by promoting lipid accumulation, oxidative stress, pro-inflammatory response, release of metalloproteinases and apoptotic cell death.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that pomegranate seed oil (PSO) has wide range of beneficial biological attributes such as immunomodulatory and anti-inflammatory, anti-cancerous, and antioxidant properties (Kim et al, 2002;Kohno et al, 2004;Lansky & Newman, 2007;Singh, Chidambara Murthy, & Jayaprakasha, 2002;Yamasaki et al, 2006). Furthermore, considering oxidative modification hypothesis and role of Ox-LDL in atherosclerosis (Pirillo, Norata, & Catapano, 2013), many studies have been conducted on using various pomegranate-derived products as natural antioxidants to improve oxidative stress and decrease atherosclerosis risk factors. Invivo and in-vitro studies have demonstrated attenuating and protective influences of the pomegranate products on LDL oxidation and atherosclerosis (Aviram et al, 2000;Basu & Penugonda, 2009;Davidson et al, 2009;Fuhrman, Volkova, & Aviram, 2005Ignarro, Byrns, Sumi, De Nigris, & Napoli, 2006;Sezer, Akçay, Ilanbey, Yıldırım, & Sözmen, 2007) through various mechanisms, including induction of paraoxonase-1 (Aviram et al, 2004) and peroxisome proliferators activated receptor (Huang et al, 2005) activities as well as endothelial nitric-oxide synthase availability , and reduction of LDL aggregation (Aviram et al, 2000) and cellular uptake of oxidized LDL (Fuhrman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%